Medical error in the courts: analysis of the Brazilian capital’s Court of Justice decisions - Delduque, Maria Célia; Montagner, Miguel; Alves, Sandra Mara Campos; Montagner, Maria Inêz; Mascarenhas, Gisela (Saúde e Sociedade, 2022)
This study investigated the medical errors and their response by the Judiciary, within the scope of Brazil’s Court of Justice of the Federal District and Territories (TJDFT), from 2002 to 2019. A documentary, qualitative, retrospective research was conducted using procedural documents contained in the lawsuits submitted to the TJDFT civil courts, analyzing the following variables: medical specialty involved, type of damage caused, public or private physician, type of claim (by the plaintiff), court decision and indemnity value, among others. Data were obtained from the court’s website, which provides full case files, and analyzed by descriptive statistics. The studied court showed a growing trend in the number of lawsuits regarding medical error, with judges sentencing physicians from public institutions with higher values. Most cases analyzed had a final unfavorable decision for the plaintiff, and even those that were successful had a reduction of approximately 30% in the amount of compensation requested. Claims for moral and material damages are the most common. TJDFT lawsuits judged over the last 17 years on medical error have grown exponentially, characterizing it as a new way to judicialize health.